Influence of Recycled High Density Polyethylene on the Conventional and Morphology Properties of Bitumen - Nazmi, W.M.; Abdul Wahab, A.F. (Journal of Engineering and Technology (JET), 2011)
The aim of this research is to evaluate the effect of recycled High Density Polyethylene (HDPE) pellet in bitumen as an additive in bitumen modification. The concentration of HDPE ranges between 1 to 5% of the weight of a soft (160/220) penetration grade bitumen were used and then compare to intermediate (100/150) penetration grade bitumen. This bitumen modification was prepared by using a high speed mixer at temperatures between 140˚C to 180˚C. The conventional tests such as penetration, softening point and visocosity were conducted to determine the basic characteristics of the HDPE modified and unmodified bitumen. Furthermore, the study on the morphology characteristic of HDPE modified bitumen was evaluated by using fluorescent microscopy to examine the degree of compatibility of the recycled HDPE pellet. The finding indicates that this bitumen modification has the ability to enhance conventional and morphology properties of bitumen. In addition, the plasticity interval and Penetration Index (PI) values of bitumen were also increased. Therefore HDPE modified bitumen can resist the previously mentioned road failures. Finally it could improve the level of performance and the service life of the road. It can be concluded that the application of HDPE modified bitumen gives more advantages compared to the neat bitumen. Having considered the environmental and economical aspects, HDPE modified bitumen is found suitable to be used for road pavements.